(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: MOW (Female Operative Method) is the act of closing both oviducts so that the egg cannot pass through the oviduct, so the egg will not meet the male’s sperm so that pregnancy does not occur. Research to determine the characteristics of Age, Parity, education, Occupation, Type of Contraception, Information, Knowledge and Interest to continue previous research in 2017, are there any differences in 2024 Banjarmasin City BKKBN Data, PIL 9.38%, Suntk 46.29%, implant 9.55%, IUD 1.99%, condom 0.28%, MOW 1.14%, MOP 0.045%. Data from RSKIA Mahkota Bunda Banjarmasin 624 people in 10 months, WUS 406 people using MOW 32 people. Objective: To determine the factors in choosing female operative contraception (MOW) in women of childbearing age (WUS) at RSKIA Mahkota Bunda Hospital, Banjarmasin. Method: Descriptive (describe). The entire population of WUS who use contraception. The sample was 41 WUS. "Accidental Sampling" sampling technique. Results: In the good knowledge category there were 26 people (63.4%), in the sufficient knowledge category there were 8 people (19.5%), and in the poor knowledge category there were 7 people (17.1%). And in the good interest category there were 13 people (31.7%), in the moderate interest category there were 12 people (29.3%), in the less interest category there were 16 people (39.0%). Conclusion: From the results of the research that has been carried out, the characteristics of Age, Parity, Education, Occupation, Type of Contraception, Information and Knowledge are in the Good category, while Interest is in the Poor category.